(untitled) (Филологические заметки, 2021)
The paper deals with the semantic analysis of Russian paremia with a lexeme beer and gives a cultural representation of the meanings and use of beer as a Russian traditional beverage. For this work, two hundred paremia were collected in which the lexeme beer (пиво) appeared, and in the analysis are included representative examples concerning the characteristics of the beverage and the specifics of its preparation. The corpus of proverbs was collected from the collections of proverbs, dictionaries, scientific articles, doctoral dissertation, and internet sources. We are interested in the meaning of beer as a beverage in Russian culture, on which occasions is consumed, whether its use is characteristic of a particular social group and what status it has had throughout the centuries as well as its role in Russian traditional culture. Since the proverbs are born from the cultural tradition itself, in seeking answers to the questions we have used data from sources that deal with cultural aspects and customs. The results of the survey show that the perception of beer is related to folk beliefs and reflects the daily life of the community in which the potion is consumed. Beer is perceived as a favourite beverage that is often consumed. It is also a potion of celebration, which expresses the hospitality and is consumed in special occasions (seasons and holidays) in a larger amount for holidays such as Maslenitsa, Easter, Christmas, but the consumption is mostly related to rest and entertainment. The producers of their own beer are characterized as wealthy and generous people who are considered superior to others.